Effects of post-anthesis heat stress on stem reserves mobilization, canopy temperature depression and floret sterility of wheat cultivars - Sikder, S; Paul, NK (Bangladesh Journal of Botany, 2010)
Testing of four heat tolerant (Gourab, Sourav, Kanchan and Shatabdi) and two heat sensitive (Sonora and Kalyansona) wheat cultivars under normal and late growing post-anthesis heat stress conditions revealed higher pre-anthesis stem reserves mobilization to the final grain weight and floret sterility in heat sensitive cultivars compared to heat tolerant cultivars. The heat tolerant cultivars showed higher canopy temperature depression than the heat sensitive cultivars in both the growing conditions indicating the higher ability of heat tolerant cultivars to maintain cooler canopy environment than the heat sensitive ones. Key words: Post-anthesis; Heat stress; Floret sterility; Canopy temperature; Mobilization DOI: 10.3329/bjb.v39i1.5526 Bangladesh J. Bot. 39(1): 51-55, 2010 (June)